Genome-Wide Identification of Circular RNAs in Arabidopsis thaliana - Chen, Gang; Cui, Jiawen; Wang, Li; Zhu, Yingfang; Lu, Zhaogeng; Jin, Biao (Frontiers in Plant Science, 2017)
Circular RNAs (circRNAs) are a family of transcripts with covalently closed circular structures and still largely unknown functions. Large numbers of circRNAs have been found in various biological processes in humans and animals, but fewer circRNAs have been identified in plants. We performed a genome-wide analysis of circRNAs in Arabidopsis thaliana via deep sequencing. We constructed 14 strand-specific libraries from 13 samples from plants from four developmental stages, four stress treatments, and five organs and a mixed sample across the lifespan. In total, we identified 5861 circRNAs, including 1275 novel ones, using the strict threshold of at least two unique back-spliced supporting reads. The circRNAs were non-randomly distributed in all chromosomes; most were exonic. Sequence similarity analysis of circRNAs between A. thaliana and four other species showed that some circRNAs are conserved in plants. Functional annotation indicated that many parent genes of circRNAs are involved in many fundamental processes including plant development, reproduction, and response to stimulus. In addition, a small proportion of circRNAs were shown to be potential targets of miRNAs, indicating that the circRNAs could interact with miRNAs to regulate gene expression. qRT-PCR analysis revealed that circRNAs displayed diverse expression patterns at different growth stages. Our results provide an important resource for continuing circRNA research in A. thaliana, and should enhance our understanding of circRNAs in plants. Key Words: Circular RNA, Parent gene, Arabidopsis, RNA-seq, Sequence conservation, MicroRNA